Interference between respiratory syncytial virus and rhinovirus in respiratory tract infections in children. (February 2016) - Karppinen, S.; Toivonen, L.; Schuez-Havupalo, L.; Waris, M.; Peltola, V.
Abstract: An acute viral respiratory tract infection might prevent infections by other viruses because of the antiviral innate immune response. However, with the use of PCR methods, simultaneous detection of two or more respiratory viruses is frequent. We analysed the effect of respiratory syncytial virus (RSV) infection on the occurrence of simultaneous rhinovirus (RV) infection in children within a birth cohort study setting. We used PCR for virus detection in nasal swabs collected from children with an acute respiratory tract infection at the age of 0–24 months and from healthy control children, who were matched for age and date of sample collection. Of 226 children with RSV infections, 18 (8.0%) had co-infections with RV, whereas RV was detected in 31 (14%) of 226 control children (p 0.049 by chi-square test). Adjustment for sex, number of siblings and socio-economic status strengthened the negative association between RSV and RV (OR 0.46, 95% CI 0.24–0.90; p 0.02). The median durations of symptoms (cough, rhinorrhoea, or fever) were 11 days in children with single RSV infections and 14 days in children with RSV–RV co-infections (p 0.02). Our results suggest that the presence of RSV reduces the probability of RV infection, but that, if a co-infection occurs, both viruses cause clinical symptoms.